2014
DOI: 10.1016/j.apsusc.2014.06.088
|View full text |Cite
|
Sign up to set email alerts
|

Study of the magnetic–Alq3 interface in organic spin-valves

Abstract: The interface between the organic semiconductor tris(8-hydrixyquinolate) aluminium (Alq 3) and two different magnetic electrodes has been investigated using X-ray photoelectron spectroscopy (XPS), Kelvin Probe, atomic force microscopy (AFM) and Magneto-optic Kerr effect (MOKE) magnetometry. The transition metal magnetic electrode/Alq 3 films were first measured using a XPS, and then washed and remeasured. It was found that Alq 3 still existed on the magnetic electrode after washing. This suggests that the Alq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The data in Table 2 show that the ratio of the metal Fe to Fe oxides to Fe satellite peak and metal Co to Co oxides to Co satellite peak, respectively, are about 49. 8 metal without oxidation is obtained. Moreover, it is acceptable for the generation of FeCo oxides because Argon ion sputter-etching itself may cause the changes of chemical states.…”
Section: Structurementioning
confidence: 98%
See 1 more Smart Citation
“…The data in Table 2 show that the ratio of the metal Fe to Fe oxides to Fe satellite peak and metal Co to Co oxides to Co satellite peak, respectively, are about 49. 8 metal without oxidation is obtained. Moreover, it is acceptable for the generation of FeCo oxides because Argon ion sputter-etching itself may cause the changes of chemical states.…”
Section: Structurementioning
confidence: 98%
“…It has been found that the interaction including interdiffusion and chemical reaction at the interface can result in a magnetic "dead" layer [5,6] during the fabrication of organic spin-valves, which could increase the spin flipping probability and reduce the spin injection efficiency. Moreover, Morley et al [7,8] reported that the chemisorptions of the organic layer onto the magnetic metal surface could also change the surface magnetization of the electrode. Majumdar et al [9] showed that separate monolayers of different organic insulators between the magnetic electrode and organic layer destroy the spin-selective interface and deteriorate spin injection.…”
Section: Introductionmentioning
confidence: 98%
“…Beyond the case of mere charge injection, metal–organic interfaces are intensively discussed in the context of spin injection and spin transport in organic materials . This includes the spin valve magnetoresistance effect, the level alignment or hybridization of states between metal and organic semiconductor, the introduction of interface layers, or effects of structurally more complex interfaces as well as spin filtering properties and the role of hybridization of interface states for spin filtering . It is therefore interesting to study both theoretically and experimentally the behavior of hot electrons/hot spins at such interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Within the field of spintronics, the spin-polarized electronic structure that occurs at the Fermi level E F of the interface between a ferromagnetic (FM) metal and a molecular semiconductor has attracted considerable interest. Indeed, the strong interfacial hybridization between FM and molecules leads to promising properties for organic spintronics , for a large variety of FM/molecule pairs and even FM/carbon . These hybridization-induced spin-polarized states are also deduced from the strong magnetic coupling that exists between paramagnetic moments localized in the molecular layer and the FM substrate. However, this hybridization can alter not only the magnetization of the FM metal’s topmost layer ,, but also delicate molecular properties such as spin crossover . Furthermore, it would be useful to allow wet chemical deposition of molecules without degrading the magnetic properties of the FM substrate.…”
mentioning
confidence: 99%